Periphyton biomass on artificial substrates during the summer and winter - Signor,Altevir (2015)
This study evaluated the periphyton production on artificial substrates considering it as a source of low cost live food for fish. Blades of artificial substrates such as wood, black plastic, acrylic, fiberglass, ceramics and glass (all with 144cm2 blades, 24 for each substrate) were submerged 20.0cm below the water column for 35 days in the winter and 42 days in the summer. The blades were randomly installed in 200m3 pond and evaluated for the biomass production at different phases during the summer and winter. Four blades of each substrate were collected weekly, and the periphytic community was carefully scraped with a spatula and fixed in 4% formaldehyde. The periphytic biomass productivity was evaluated by artificial substrate area and per day. The results evidenced the characteristic periodicity in periphyton biomass production and a significant variability in the collect period and season in the different artificial substrates used. Ceramic and wood showed the best results in the summer while wood showed the best results in the winter. The priphyton biomass productions differ among periods, substrates and seasons. Wood and ceramics could be indicated for periphyton biomass production in either winter or summer.